Recurrence of Immunotactoid Glomerulopathy with Monoclonal IgG3κ Deposits after Kidney Transplant - Katsuyuki Miki; Maki Sumida; Kazuhiro Iwadoh; Kazuho Honda; Toru Murakami; Ichiro Koyama; Ichiro Nakajima; Shohei Fuchinoue (Archives of Organ Transplantation - Peertechz Publications, 2017)
We report a case of rapid recurrence of immunotactoid glomerulopathy (ITG) with monoclonal IgG3κ deposits in a transplanted renal graft. A 55-year-old hemodialysis male patient due to ITG underwent an ABO-incompatible living-donor kidney transplantation. Proteinuria (3.11 g/day) and increased serum creatinine (2.52 mg/dL) were detected on postoperative day (POD) 4 due to acute antibody-mediated rejection (aAMR). Even after treatment for aAMR, proteinuria increased again to 4.5 g/day because of a recurrent ITG with IgG3κ subclass deposits. He returned to maintenance hemodialysis 9 months after transplantation.  This case underlines the importance of preoperative monoclonal paraproteinuria test to predict an ITG recurrence in the renal graft.